High-strength impervious concrete and preparation method thereof

By using fiber reinforcement and specific anti-seepage agent of modified sepiolite fiber and polyvinyl alcohol fiber in high-strength concrete, the problems of decreasing strength and poor anti-seepage properties of high-strength concrete after water absorption in humid environments are solved, and the effects of high strength, good impermeability and long service life are achieved.

CN119822750AActive Publication Date: 2025-04-15LINYI SANFANG REAL ESTATE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510151960.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-15
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

After the existing high-strength concrete absorbs water in a humid environment, the unhydrated cement particles continue to hydrate, resulting in internal expansion stress, microcracks, and reduced strength and anti-seepage properties.

Method used

A fiber reinforcement is used to form a mass ratio of modified sepiolite fiber and polyvinyl alcohol fiber at a 3:1 ratio, and is equipped with anti-impermeable agents such as sodium lignin sulfonate, tetramethyldivinyldisiloxane, neodymium chloride, etc. to enhance its compressive, split strength and anti-impermeable properties by improving the internal microstructure of concrete.

Benefits of technology

It significantly improves the compressive, tensile strength and permeability of concrete, extends its service life, and meets the high requirements for durability and strength in modern construction projects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses high-strength impervious concrete which is prepared from the following raw materials in parts by weight: 200-260 parts of cement, 100-140 parts of coarse aggregate, 200-220 parts of fine aggregate, 60-100 parts of fly ash, 20-30 parts of a fiber reinforcing agent, 10-20 parts of an impervious agent, 3-5 parts of a water reducing agent and 100-120 parts of water. The fiber reinforcing agent is prepared from modified sepiolite fiber and polyvinyl alcohol fiber according to the mass ratio of 3: 1; the anti-permeability agent is composed of sodium lignin sulfonate, tetramethyl divinyl disiloxane and neodymium chloride according to the mass ratio of 1: (2-4): (0.5-0.8). The prepared concrete has a better internal microstructure, good compactness, excellent compression resistance, splitting tensile strength and impermeability, good overall performance and good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to high-strength impermeability concrete and a preparation method thereof. Background Art

[0002] In recent years, my country's construction projects have developed rapidly, but ordinary cement concrete has the defects of poor toughness, durability, crack resistance and brittleness, which makes it difficult to meet the requirements of good durability and high strength of modern construction projects. Therefore, with the improvement of the performance requirements of buildings for concrete, high-strength concrete has become the representative of modern concrete technology and the future development direction. However, high-strength concrete also has the disadvantages of high brittleness, low tensile strength and poor crack resistance. There are many unhydrated cement particles in high-strength concrete, which almost account for 40% to 70% of the total cement. In a humid environment, after high-strength concrete absorbs water, the unhydrated cement inside will continue to hydrate, and the volume of the generated hydration product will be significantly larger than the volume of the original cement, and the hydration product will gradually fill the internal pores of the concrete; if the reaction continues, the volume of the cement hydration product will be larger than the volume of the internal pores of the concrete, thereby generating expansion stress inside the concrete, resulting in more microcracks in the concrete, which leads to a decrease in strength and poor impermeability. Therefore, it is of great significance to improve the impermeability and strength of concrete. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength impermeability concrete, which has the advantages of high strength, good impermeability and long service life, and can better meet the needs of modern concrete engineering.

[0004] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0005] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 200-260 parts of cement, 100-140 parts of coarse aggregate, 200-220 parts of fine aggregate, 60-100 parts of fly ash, 20-30 parts of fiber reinforcement, 10-20 parts of impermeability agent, 3-5 parts of water reducer, and 100-120 parts of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:2-4:0.5-0.8.

[0006] Preferably, the modified sepiolite fiber is prepared by the following method:

[0007] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed uniformly in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried to obtain a solid material A;

[0008] (2) taking sepiolite fiber and adding it to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. and reacting for 2-3 hours, after the reaction is completed, filtering to obtain the treated solid fiber, washing it with deionized water for more than 3 times, and drying to obtain the amino-modified sepiolite fiber;

[0009] (3) Solid material A and amino-modified sepiolite fiber were mixed according to a mass ratio, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0010] Preferably, in step (1), the usage ratio of the graphene oxide powder and the nano-silicon dioxide powder mixture, the hydrochloric acid solution, the aniline, and the ammonium persulfate is 5 g:100 ml:0.1-0.15 mol:0.12-0.18 mol.

[0011] Preferably, in step (2), the mass volume ratio of sepiolite fiber, ethylenediamine solution and aluminum chloride is 5-8g:200ml:0.5g.

[0012] Preferably, in step (3), the mass ratio of solid matter A to amino-modified sepiolite fiber is 1:4.

[0013] Preferably, the water reducer is a naphthalene-based water reducer or a polycarboxylic acid-based high-efficiency water reducer.

[0014] Preferably, the cement is ordinary Portland cement.

[0015] The present invention also provides a method for preparing the above-mentioned high-strength impermeability concrete, which comprises the following steps:

[0016] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0017] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0018] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0019] Adding fiber as reinforcing material to concrete material can improve the strength, durability, crack resistance and overall performance of concrete, for example, basalt fiber, steel fiber, polyvinyl alcohol fiber, etc. can be added. Because the fiber of different properties has a greater impact on the performance of concrete after being added. The present invention adopts the method of mixing modified sepiolite fiber with polyvinyl alcohol fiber (PVA) to improve the strength and impermeability of concrete, wherein the PVA fiber can effectively improve the impermeability of concrete by limiting the expansion of cracks inside concrete; the modified sepiolite fiber is obtained by further modifying the composite material formed by sepiolite fiber with surface amino modification and silicon dioxide, polyaniline and graphene oxide, wherein the composite material formed by silicon dioxide, polyaniline and graphene oxide is rich in groups such as hydroxyl, carboxyl and epoxy groups, these groups can form a stable combination with the amino groups on the surface of sepiolite through electrostatic attraction or covalent bonding, enhance interface stability, and show higher interface bonding strength and mechanical properties when used in concrete. At the same time, the addition of modified sepiolite fibers forms a large number of needle-shaped calcium aluminate and flaky calcium hydroxide crystals inside, which effectively improves the density of the mortar hardening system, thereby improving the strength and impermeability of concrete.

[0020] The anti-seepage agent used in the present invention is composed of sodium lignin sulfonate, tetramethyl divinyl disiloxane and neodymium chloride in a specific ratio. Sodium lignin sulfonate improves the density of concrete by water reduction, the hydrophobicity of tetramethyl divinyl disiloxane further reduces water penetration, and neodymium chloride further enhances the density of concrete by accelerating cement hydration reaction. The synergistic effect between the three enhances the interface bonding between the cement matrix and the aggregate, reduces interface defects, and thus improves the overall performance of the concrete. When used in combination with the fiber reinforcement prepared by the present invention, the synergistic effect is significant, and the strength, durability, crack resistance and overall performance of the concrete can be significantly improved.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The fiber reinforcement made of modified sepiolite fiber and polyvinyl alcohol fiber in proportion is mixed with other raw materials, and the obtained concrete has excellent compressive strength, splitting tensile strength and impermeability, good overall performance and good market application prospects.

[0023] 2) Select appropriate proportions of anti-seepage agent and fiber reinforcement agent in combination, and the raw materials complement each other to further optimize the internal microstructure composition of concrete, improve the density of concrete, and further improve the anti-seepage performance of concrete. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto. The raw materials used in the embodiments of the present invention are commercially available unless otherwise specified, wherein the cement is PO 42.5 cement; the fly ash is Class I fly ash, the sepiolite fiber length is 1-5 mm, and the polyvinyl alcohol fiber length is 9-12 mm.

[0025] Example 1

[0026] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 240kg of cement, 120kg of coarse aggregate, 210kg of fine aggregate, 80kg of fly ash, 25kg of fiber reinforcement, 15kg of impermeability agent, 4kg of water reducer, and 110kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:2:0.5.

[0027] The modified sepiolite fiber is prepared by the following method:

[0028] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.1 mol:0.12 mol;

[0029] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 5 g:200 ml:0.5 g;

[0030] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0031] The water reducer is a naphthalene-based water reducer; and the cement is ordinary Portland cement PO 42.5.

[0032] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0033] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0034] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0035] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0036] Example 2

[0037] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 200kg of cement, 100kg of coarse aggregate, 200kg of fine aggregate, 60kg of fly ash, 20kg of fiber reinforcement, 10kg of impermeability agent, 3kg of water reducer, and 100kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:4:0.8.

[0038] The modified sepiolite fiber is prepared by the following method:

[0039] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.15 mol:0.18 mol;

[0040] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. and reacting for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 8 g:200 ml:0.5 g;

[0041] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0042] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0043] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0044] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0045] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0046] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0047] Example 3

[0048] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0049] The modified sepiolite fiber is prepared by the following method:

[0050] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0051] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0052] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0053] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0054] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0055] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0056] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0057] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0058] Comparative Example 1

[0059] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0060] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0061] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0062] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0063] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0064] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0065] The comparative example is basically the same as Example 3, except that the fiber reinforcement is composed of unmodified sepiolite fiber and polyvinyl alcohol fiber.

[0066] Comparative Example 2

[0067] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0068] The modified sepiolite fiber is prepared by the following method:

[0069] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0070] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0071] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 2:1, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0072] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0073] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0074] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0075] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0076] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0077] The comparative example is basically the same as Example 3, except that the modified sepiolite fiber is prepared by mixing the solid material A and the amino-modified sepiolite fiber in a mass ratio of 2:1.

[0078] Comparative Example 3

[0079] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0080] The modified sepiolite fiber is prepared by the following method:

[0081] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0082] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0083] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:1, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0084] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0085] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0086] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0087] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0088] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0089] The comparative example is basically the same as Example 3, except that the modified sepiolite fiber is prepared by mixing the solid material A and the amino-modified sepiolite fiber in a mass ratio of 1:1.

[0090] Comparative Example 4

[0091] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0092] The modified sepiolite fiber is prepared by the following method:

[0093] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0094] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0095] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:2, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0096] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0097] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0098] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0099] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0100] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0101] The comparative example is basically the same as Example 3, except that the modified sepiolite fiber is prepared by mixing the solid material A and the amino-modified sepiolite fiber in a mass ratio of 1:2.

[0102] Comparative Example 5

[0103] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:3:0.6.

[0104] The modified sepiolite fiber is prepared by the following method:

[0105] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0106] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0107] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:6, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0108] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0109] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0110] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0111] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0112] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0113] The comparative example is basically the same as Example 3, except that the modified sepiolite fiber is prepared by mixing the solid material A and the amino-modified sepiolite fiber in a mass ratio of 1:6.

[0114] Comparative Example 6

[0115] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260 kg of cement, 140 kg of coarse aggregate, 220 kg of fine aggregate, 100 kg of fly ash, 30 kg of fiber reinforcement, 5 kg of water reducer, and 120 kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1. The modified sepiolite fiber is prepared by the following method:

[0116] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0117] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0118] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0119] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0120] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0121] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0122] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0123] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0124] The above comparative example is basically the same as Example 3, except that it does not contain an anti-seepage agent.

[0125] Comparative Example 7

[0126] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate and tetramethyldivinyldisiloxane in a mass ratio of 1:3.

[0127] The modified sepiolite fiber is prepared by the following method:

[0128] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0129] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0130] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0131] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0132] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0133] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0134] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0135] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0136] The above comparative example is basically the same as Example 3, the only difference being that the anti-seepage agent does not contain neodymium chloride.

[0137] Comparative Example 8

[0138] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of sodium lignin sulfonate and neodymium chloride in a mass ratio of 1:0.6.

[0139] The modified sepiolite fiber is prepared by the following method:

[0140] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0141] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0142] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0143] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0144] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0145] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0146] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0147] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0148] The above comparative example is basically the same as Example 3, except that the anti-seepage agent does not contain tetramethyldivinyldisiloxane.

[0149] Comparative Example 9

[0150] A high-strength impermeable concrete is made of the following raw materials in parts by weight: 260kg of cement, 140kg of coarse aggregate, 220kg of fine aggregate, 100kg of fly ash, 30kg of fiber reinforcement, 20kg of impermeability agent, 5kg of water reducer, and 120kg of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the impermeability agent is composed of tetramethyldivinyldisiloxane and neodymium chloride in a mass ratio of 1:3:0.6.

[0151] The modified sepiolite fiber is prepared by the following method:

[0152] (1) Graphene oxide powder and nano-silicon dioxide powder were mixed in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried to obtain a solid material A; wherein the amount ratio of the mixture of graphene oxide powder and nano-silicon dioxide powder, hydrochloric acid solution, aniline, and ammonium persulfate was 5 g:100 ml:0.12 mol:0.16 mol;

[0153] (2) Adding sepiolite fiber to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. for reaction for 2-3 hours, filtering to obtain the treated solid fiber after the reaction, washing with deionized water for more than 3 times, and drying to obtain amino-modified sepiolite fiber; wherein the mass volume ratio of sepiolite fiber, ethylenediamine solution, and aluminum chloride is 6 g:200 ml:0.5 g;

[0154] (3) Solid material A and amino-modified sepiolite fiber were mixed in a mass ratio of 1:4, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

[0155] The water reducer is a polycarboxylate water reducer; and the cement is ordinary Portland cement PO 42.5.

[0156] The method for preparing the above-mentioned high-strength impermeable concrete comprises the following steps:

[0157] S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix;

[0158] S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to mix and mix evenly to obtain a mixed slurry;

[0159] S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

[0160] The above comparative example is basically the same as Example 3, except that the anti-seepage agent does not contain sodium lignin sulfonate.

[0161] Performance Testing

[0162] Take the high-strength impermeable concrete of Examples 1-3 and Comparative Examples 1-9, pour the slurry into a test mold with a size of 100mm×100mm×100mm, demould after molding for 24 hours, and put the demoulding sample into a standard curing box with a temperature of (20±2)℃ and a relative humidity of >95% for curing for 28 days; according to the national standard GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the mechanical properties are measured, including compression test and splitting strength test. According to the national standard GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the impermeability is measured, the sample size penetration pressure is 1MPa, the pressurization time is 48h, and the specific test results are shown in Table 1.

[0163] Table 1 Test results

[0164] Compressive strength(MPa) Splitting tensile strength(MPa) Water seepage height (mm) Example 1 68.6 6.95 0.25 Example 2 65.9 6.89 0.19 Example 3 67.5 6.77 0.23 Comparative Example 1 55.6 5.09 1.68 Comparative Example 2 52.9 5.02 2.01 Comparative Example 3 55.9 5.53 0.53 Comparative Example 4 60.5 5.92 0.35 Comparative Example 5 58.9 5.47 0.32 Comparative Example 6 53.1 5.06 1.99 Comparative Example 7 59.5 5.98 1.12 Comparative Example 8 60.2 6.12 0.89 Comparative Example 9 58.7 6.06 1.22

[0165] It can be seen from the data in Table 1 that the compressive strength, splitting tensile strength and impermeability strength of the concrete prepared by Examples 1-3 of the present invention are better than those of Comparative Examples 1-9. It can be seen from the data of Comparative Examples 1-5 that the addition of modified sepiolite fibers in the concrete of the present invention can improve the mechanical properties of the concrete compared with Comparative Example 1 of unmodified sepiolite fibers, and it can be seen from the data of Comparative Examples 2-5 that the modification method of the modified sepiolite fibers has a greater impact on the performance of the concrete. When the amount of solid A and the solid A in the amino-modified sepiolite fibers is too much, the performance of the concrete is reduced instead. This is because too much graphene oxide and silicon dioxide are easily agglomerated in the concrete. This agglomeration phenomenon will reduce the dispersibility of the material, resulting in an uneven internal structure of the concrete, thereby reducing the performance. In addition, excessive use also leads to increased costs; and if the amount of solid A is too little, it cannot play a good synergistic role with the amino-modified sepiolite fibers to achieve a good effect of enhancing interface stability and improving the interface bonding strength and mechanical properties of the concrete. It can be seen from the results of Comparative Examples 6-9 that by changing the composition of the anti-seepage agent, the mechanical properties of the concrete will be weakened accordingly, which shows that the raw materials constituting the anti-seepage agent of the present invention complement each other and are indispensable. They work together with the fiber reinforcement agent and other raw materials to prepare a high-strength anti-seepage concrete, which has broad market application prospects.

[0166] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A high-strength impermeable concrete, characterized in that: It is made of the following raw materials in parts by weight: 200-260 parts of cement, 100-140 parts of coarse aggregate, 200-220 parts of fine aggregate, 60-100 parts of fly ash, 20-30 parts of fiber reinforcement, 10-20 parts of anti-seepage agent, 3-5 parts of water reducer, and 100-120 parts of water; the fiber reinforcement is composed of modified sepiolite fiber and polyvinyl alcohol fiber in a mass ratio of 3:1; the anti-seepage agent is composed of sodium lignin sulfonate, tetramethyldivinyldisiloxane, and neodymium chloride in a mass ratio of 1:2-4:0.5-0.

8.

2. The high-strength impermeable concrete according to claim 1, characterized in that: The modified sepiolite fiber is prepared by the following method: (1) Graphene oxide powder and nano-silicon dioxide powder were mixed uniformly in a mass ratio of 1:3, added to a 2 mol / L hydrochloric acid solution, ultrasonically dispersed for 10-15 min, and then aniline and ammonium persulfate were added thereto. The mixture was stirred and reacted at room temperature for 24 h. The reaction product was centrifuged and the obtained solid product was washed with deionized water and anhydrous ethanol for 3 times respectively, and dried to obtain a solid material A; (2) taking sepiolite fiber and adding it to a 0.2 mol / L ethylenediamine solution, adding aluminum chloride, stirring evenly, heating the mixture to 60-65° C. and reacting for 2-3 hours, after the reaction is completed, filtering to obtain the treated solid fiber, washing it with deionized water for more than 3 times, and drying to obtain the amino-modified sepiolite fiber; (3) Solid material A and amino-modified sepiolite fiber were mixed according to a mass ratio, and then mechanically ground at a speed of 100 r / min for 1 h. The mixture was then ultrasonically dispersed for 30 min to obtain modified sepiolite fiber.

3. The high-strength impermeable concrete according to claim 2, characterized in that: In step (1), the usage ratio of the graphene oxide powder and the nano-silicon dioxide powder mixture, the hydrochloric acid solution, the aniline and the ammonium persulfate is 5g:100ml:0.1-0.15mol:0.12-0.18mol.

4. The high-strength impermeable concrete according to claim 2, characterized in that: In step (2), the mass volume ratio of sepiolite fiber, ethylenediamine solution and aluminum chloride is 5-8g:200ml:0.5g.

5. The high-strength impermeable concrete according to claim 2, characterized in that: In step (3), the mass ratio of solid material A to amino-modified sepiolite fiber is 1:

4.

6. The high-strength impermeable concrete according to claim 1, characterized in that: The water reducer is a naphthalene-based water reducer or a polycarboxylic acid-based high-efficiency water reducer.

7. The high-strength impermeable concrete according to claim 1, characterized in that: The cement is ordinary Portland cement.

8. A method for preparing high-strength impermeable concrete according to any one of claims 1 to 7, characterized in that: It includes the following steps: S1: Mix cement, coarse aggregate and fine aggregate and stir them evenly to obtain a premix; S2: adding fly ash and fiber reinforcement into the premix and mixing them evenly, and adding water, anti-seepage agent and water reducing agent and continuing to stir and mix evenly to obtain a mixed slurry; S3: The slurry is poured, formed and cured to produce a finished high-strength and impermeable concrete.

Citation Information

Patent Citations

  • Nano inorganic enhancer

    CN106904860A

  • Anti-seepage and anti-cracking concrete and preparation method thereof

    CN113402222A